Chronic Stress Modulates Interneuronal Plasticity: Effects on PSA-NCAM and Perineuronal Nets in Cortical and Extracortical Regions - Pesarico, Ana Paula; Bueno-Fernandez, Clara; Guirado, Ramón; Gómez-Climent, María Ángeles; Curto, Yasmina; Carceller, Hector; Nacher, Juan (Frontiers in Cellular Neuroscience, 2019)
Chronic stress has an important impact on the adult brain. However, most of the knowledge on its effects is focused on principal neurons and less on inhibitory neurons. Consequently, recent reports have begun to describe stress-induced alterations in the structure, connectivity and neurochemistry of interneurons. Some of these changes appear to be mediated by certain molecules particularly associated to interneurons, such as the polysialylated form of the neural cell adhesion molecule (PSA-NCAM) and components of the perineuronal nets (PNN), specialized regions of the extracellular matrix. These plasticity-related molecules modulate interneuronal structure and connectivity, particularly of parvalbumin expressing basket interneurons, both during development and adult life. These inhibitory neurons are specially affected after chronic stress and in some stress-related disorders, in which the expression of PSA-NCAM and certain components of PNN are also altered. For these reasons we have decided to study PSA-NCAM, PNN and parvalbumin expressing interneurons after 10 days of chronic restraint stress, a time point in which its behavioral consequences are starting to appear. We have focused initially on the medial prefrontal cortex (mPFC), basolateral amygdala (BLA) and hippocampus, regions affected by stress and stress-related psychiatric diseases, but we have also explored the habenula and the thalamic reticular nucleus due to the important presence of PNN and their relationship with certain disorders. PSA-NCAM expression was increased by stress in the stratum lacunosum-moleculare of CA1. Increases in parvalbumin immunoreactive cells were detected in the mPFC and the BLA, but were not accompanied by increases in the number of parvalbumin expressing perisomatic puncta on the somata of principal neurons. The number of PNN was also increased in the mPFC and the habenula, although habenular PNN were not associated to parvalbumin cells. Increased expression of parvalbumin and components of PNN were also detected in the thalamic reticular nucleus after chronic restraint stress, revealing for the first time substantial effects on this region. Our study shows that, even a short chronic stress protocol, can induce consistent changes in interneuronal plasticity-related molecules in cortical and extracortical regions, which may represent initial responses of inhibitory circuits to counteract the effects of this aversive experience.